2004
DOI: 10.1177/1043986204263770
|View full text |Cite
|
Sign up to set email alerts
|

White-Collar Crime and Criminal Careers

Abstract: The life course approach to the study of criminal careers has achieved a prominent place in criminology. Life course researchers have identified several distinct patterns in criminal offending and provided several provocative explanations to account for them. Noticeably lacking in the study of life course criminology, however, is any recognition of white-collar offenders. The typical whitecollar offender greatly differs from the typical street offender and does not appear to fit into the proposed explanations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…There is some evidence to suggest that the traditional age crime curve does not reflect patterns of participation in white collar crime (e.g. Piquero and Benson, 2004), and more recent research has identified divergences in offending patterns and criminal trajectories across a sample of people convicted of white collar crime (e.g. Onna et al, 2014).…”
Section: The Age Crime Curvementioning
confidence: 99%
“…There is some evidence to suggest that the traditional age crime curve does not reflect patterns of participation in white collar crime (e.g. Piquero and Benson, 2004), and more recent research has identified divergences in offending patterns and criminal trajectories across a sample of people convicted of white collar crime (e.g. Onna et al, 2014).…”
Section: The Age Crime Curvementioning
confidence: 99%
“…Researchers have not specifically applied life course theory to elder neglect, but some have shown how the theory relates to elder abuse in general (Payne & Gainey, 2009). Also, researchers have called for the use of life course theory to explain crimes committed at work (Benson & Kerley, 2000;Piquero & Benson, 2004).…”
Section: Review Of Literaturementioning
confidence: 98%
“…Social influence as a motivational matter is related to situational factors that trigger the offenders (Piquero & Benson, 2004), and these factors include the need for control, risk-option decision making, and fear of falling (Bucy et al, 2008;Shover et al, 2012). The need for control refers to individuals who are assertive, decisive, and active.…”
Section: Motivationmentioning
confidence: 99%
“…The issue concerns the differences between the ‗one-timer' and the career criminal (those with four or more convictions) concerning background, occupational career, family life, etc. The life-course approach has begun to catch on in investigations of street criminality, especially juvenile delinquency, but it has not yet reached the field of white collar crime to a significant degree (Piquero & Benson, 2004). …”
Section: Career Criminalitymentioning
confidence: 99%
See 1 more Smart Citation